Pre‐operative nutrition and the elective surgical patient: why, how and what?. (2nd January 2019) - Gillis, C.; Wischmeyer, P. E.
Summary: Pre‐operative nutrition therapy is increasingly recognised as an essential component of surgical care. The present review has been formatted using Simon Sinek's Golden Circle approach to explain 'why' avoiding pre‐operative malnutrition and supporting protein anabolism are important goals for the elective surgical patient, 'how' peri‐operative malnutrition develops leading in part to a requirement for pre‐operative anabolic preparation, and 'what' can be done to avoid pre‐operative malnutrition and support anabolism for optimal recovery.